Kajian Diftong Dan Gugus Konsonan Pada Bacaan Anak Mengarungi Samudera Kehidupan Karya Muh. Sunardiyanto. - Melsa Nuraisyah; Selfi Novita Mariam; Welly Karmelia (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Analyzing the study of diphthongs and consonant clusters in the children's reading book